1990
DOI: 10.1007/bf00006227
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgal assemblages in New Zealand: structure, interactions and demography

Abstract: Quantitative descriptions of macroalgal distributions from low intertidal regions to a sublittoral depth of 20 m are presented for rocky reefs from several localities ranging over 16°latitude in New Zealand. These include the northern and southern main islands as well as the Chatham Islands and the sub-antarctic Auckland Islands. Fucalean algae are dominant in the shallow sublittoral regions throughout NZ. Laminarian species are rare and generally reach their greatest abundances at 7-17 m depth. The colder wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
82
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 57 publications
(93 reference statements)
6
82
0
Order By: Relevance
“…data). Both the fauna of fishes (Francis 1996, Schiel & Hickford 2001) and the macroalgal flora (Schiel 1990) in more southern regions are distinct from those of more intensively studied regions such as northeastern New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…data). Both the fauna of fishes (Francis 1996, Schiel & Hickford 2001) and the macroalgal flora (Schiel 1990) in more southern regions are distinct from those of more intensively studied regions such as northeastern New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…Temperate reefs in the southern hemisphere lack the strongylocentrotid sea urchins which dominate the most-studied sites in the northern hemisphere (Chapman & Johnson 1990;Foster 1990), and historically the predatory faunas of the hemispheres may have differed considerably (Estes & Steinberg 1988). There have been reviews of Australian (Underwood & Kennelly 1990), South African (Branch & Griffiths 1988), South American (Santelices 1990), and New Zealand (Schiel 1988(Schiel , 1990) seaweed stands. There are, however, few longterm studies of macroalgal forests in the southern hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of the distribution and abundance of adult sea urchin and abalone populations demonstrated strong spatial segregation on spatial scales ranging from individual crevices to larger habitat patches (Lowry and Pearse 1973, Shepherd 1973b, Schiel 1990, Andrew and Underwood 1992. For example, in New Zealand, the large sea urchin Evechinus chloroticus typically occupies deeper depth strata than the blackfoot abalone, Haliotis iris, which tend to aggregate in the shallow, wave-exposed subtidal (Schiel 1990, McShane andNaylor 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently Strain and Johnson (2009) (Strain and Johnson 2013). While clearly the strength and nature of trophic interactions depend strongly on sea urchin-abalone species combinations, a consistent pattern in maintenance of habitat complexity by exclusion of sea urchins is often observed in systems where a strong spatial segregation between species is maintained (Shepherd 1973b, Schiel 1990, Andrew et al 1998.…”
Section: Introductionmentioning
confidence: 99%